Літологічна характеристика та умови осадконакопичення горбашівської світи нижнього венду Волині - Іванченко, К.В. (Інститут геологічних наук НАН України, 2009)
Описано два вида разрезов горбашевской свиты. Рассмотрено их распространение, строение, состав и условия осадконакопления. Two types of cross-sections of Gorbashiv Formation are described. Their spreading, structure, composition and sedimentation conditions are examined.